Occupational Risk Factors for Arterial Hypertension in Workers of High Speed Railway Line in Italy - Norma Barbini; Martina Speziale; Rosa Squadroni (Archives of Clinical Hypertension - Peertechz Publications, 2017)
Few studies have examined the professional risk factors for hypertension, especially in relation to aging of work force. This paper shows which working risk factors represent a major risk factor for arterial hypertension in workers who work in the construction of the railway line "TAV" (High-speed trains) for the connection between Italy and France. A population of workers TAV were examined by questionnaires survey Estev, validated in France. Arterial pressure, obtained after about 30 minutes after the end of the work, was measured in clinostatic position, measuring it three times and using the average value obtained. Subjects considered high-blood pressure sufferers presented values of systolic arterial pressure higher than 140 mmHg, and/or a diastolic pressure equal or higher than 90 mmHg, following the criteria indicated by the WHO. The champion of workers were all male. In more of the half of sample was found high blood pressure. The data analysis showed the highest prevalence of hypertension in the drivers of heavy vehicles. The job that requires prolonged attention was resulted the main occupational risk factor associated with  hypertension. The excess of risk for the over 45 year olds requires corrective interventions of an organizational nature, like for example the alternation of heavier tasks and/or the increase of work breaks, to allow older workers to dilute the amount of work load and reduce the chances of arterial hypertension risk and more in general of risks for the cardiovascular system.